ANALISIS PENDAPATAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI SAWAH DI DESA AERAMO KECAMATAN AESESA KABUPATEN NAGEKEO - Ernesta Ito; Fidelis Klau; Kudji Herewila (Undana Press, 2021)
This research was conducted in Aeramo Village Aesesa District Nagekeo Regency in February - March 2020. This research aims to find out: (1) The amount of rice farming income in the first growing season of 2019 (2) factors that affect rice field production. The data collection method used in this study is the survey method. . 69 respondents who had been proportional random sampling method. The types of data collected are primary and secondary data. The data and information obtained are analyzed quantitatively. To answer the first goal the data is analyzed using revenue analysis, while to answer the second goal the data is analyzed using analysis of Cobb-Douglas production functions. The results showed that (1) the total income of rice farming in Aeramo Village amounted to Rp 591,195,000 with an average per farmer respondent of Rp 8,568,043/res. (2) Production factors analyzed using the Cobb-douglas method obtained the following models: Y = 3.807 + 0.306X1 + 0.222X2 + 0.451X3 + 0.023X4 – 0.076X5 – 0.028X6 -0.037X7. From the results of the analysis is known Determination Coefficient (R2) of 0.853 which means the area of land, seeds, fertilizers, pesticides, labor, agricultural experience and formal education affects rice paddy production by 85% while the remaining 15% is influenced by other factors that are not studied. F test results showed that production factors together influenced rice paddy production. T test results showed that the widespread factors of land, seeds, fertilizers had a real effect on rice production while pesticides, labor, agricultural experience and formal education had no real effect on rice production.